Early fast‐acting treatment strategy against generalized myasthenia gravis. Issue 6 (3rd February 2017) - Utsugisawa, Kimiaki; Nagane, Yuriko; Akaishi, Tetsuya; Suzuki, Yasushi; Imai, Tomihiro; Tsuda, Emiko; Minami, Naoya; Uzawa, Akiyuki; Kawaguchi, Naoki; Masuda, Masayuki; Konno, Shingo; Suzuki, Hidekazu; et al.
ABSTRACT: Introduction: In this study we sought to clarify the effects of early fast‐acting treatment (EFT) strategies on the time course for achieving the treatment target in generalized myasthenia gravis (MG). Methods: This retrospective study of 923 consecutive MG patients analyzed 688 generalized MG patients who had received immunotherapy during the disease course. The time to first achieve minimal manifestations (MM) or better while receiving prednisolone at ≤5 mg/day for ≥6 months (MM‐or‐better‐5mg) up to 120 months after starting immunotherapy was compared between EFT and non‐EFT patients. Results: Achievement of MM‐or‐better‐5mg was more frequent and earlier in the EFT group ( P = 0.0004, Wilcoxon test; P = 0.0001, log‐rank test). Multivariate Cox regression analysis calculated a hazard ratio of 1.98 ( P < 0.0001) for utilization of EFT. Dosing regimens of oral steroids in EFT produced no differences in the time course. Conclusions: EFT strategies are advantageous for early achievement of MM‐or‐better‐5mg. Muscle Nerve 55 : 794–801, 2017